Planowanie przestrzeni publicznej na wsi w województwie warmińsko-mazurskim = Planning public space in the rural areas of the Warmińsko-Mazurskie Voivodship - Jaszczak, Agnieszka. Autor (PAN IGiPZ, 2019)
Planning the public space as part of the “village renewal” should be based on rural identity and its traditions, but on the other hand also on contemporary design trends. “Village renewal” is a joint action of local authorities, experts and – above all – inhabitants, aimed at improving the quality of life, aesthetics of the surrounding area, protecting and shaping the landscape, and implementing social initiatives. In the region of Warmia and Masuria, the Marshal Office plays a special role in accomplishing the “renewal” tasks. Regional authorities coordinate the renewal program and undertake numerous social and cultural initiatives, organize trainings, conferences and thematic workshops. The paper briefly presents the role of the “Village Renewal Program” in the context of planning the public space. Main assumptions for creating such space based on social participation and expert assistance were also determined. The author presented examples of projects in selected villages of the Warmińsko-Mazurskie Voivodship, including these from the “Active Village of Warmia, Masuria and Powiśle” program. The paper highlighted positive results of these activities, but has also referred to existing problems.
24 cm
Keywords: public space; village renewal; green areas; aestheticization of villages; Warmińsko-Mazurskie voivodship

Partycypacja społeczna w rozwoju lokalnym na przykładzie gmin w Specjalnej Strefie Włączenia województwa zachodniopomorskiego = Social participation in local development on the example of municipalities in the Special Inclusion Zone of Zachodniopomorskie Voivodeship - Mazurek, Damian. Autor (PAN IGiPZ, 2019)
The importance of society in shaping spatial order is increasingly emphasized in research as well as in the creation of local politics. Social potential and its importance in development is the subject of research of both sociologists and geographers. The article addresses issues related to the relationship between the level of social potential and the degree of involvement of local communities in development. An analysis of ventures indicated by local communities to solve the diagnosed problems was also conducted. Data was used for municipalities indicated as problem areas and qualified for the so-called Special Inclusion Zone of Zachodniopomorskie Voivodeship from revitalization programs. The analysis also used statistical data from the Central Statistical Office to calculate the synthetic indicator of social potential. The results show that in areas with low social potential, residents show more revitalization initiatives, but are limited to infrastructural needs.
24 cm
Keywords: social participation; social potential; local development; degradated area; area of revitalization; Special Inclusion Zone; Zachodniopomorskie voivodship

Specyfika wojewódzkich programów odnowy wsi w Polsce w kontekście literatury naukowej = Specificity of the regional village renewal programmes in Poland in the context of academic studies - Wolski, Oskar (PAN IGiPZ, 2017)
Village renewal has been realised in Poland via regional village renewal programmes since 1997. The programmes have differed from each other and consequently they have implemented renewal in a diverse way. Moreover, one should note that there is a dissonance between what village renewal is in practice and what it should be according to academics. The paper possesses two aims: 1) to determine characteristics of the regional village renewal programmes in Poland and to reveal how they correspond to particular village renewal dimensions (physical-spatial, economic and social), 2) to determine the extent to which the programmes refer to village renewal features and fulfil its aims in the context of the academic theory of village renewal. More than 350 regional councils and boards’ resolutions and attachments to resolutions up to and including the year 2016 have been analysed. These include regions where the village renewal programmes operated in the past or are still in operation. Where appropriate, the author contacted respective marshal offices to obtain information. Moreover, literature review has been conducted. Selected conclusions: 1) regarding general principles of the regional village renewal programmes -they are similar to each other, and the village renewal has got broad aims and contributes to each dimension, 2) the following types of the regional programmes can be identified: „incentive”, „subsidy” and mixed, 3) the general principles of the regional programmes many times overestimated the results of the operations conducted as part of the programmes, given the aims of the operations and their expenditure, 4) concerning the operations themselves, these fulfil only the physical-spatial and partly the social dimension of the renewal.
24 cm
Keywords: village renewal; regional village renewal programmes; rural areas development; dimensions of village renewal

Zasoby lokalne, odnowa wsi i koncepcje rozwoju obszarów wiejskich. Próba teoretycznego ujęcia zależności = Local resources, village renewal and rural development concepts. An attempt to theoretical view on relations - Wolski, Oskar; Sykała, Łukasz (PAN IGiPZ, 2016)
Village renewal is currently being more and more highlighted as an element of ruralspace changes, both in terms of practical and theoretical context. The way the village renewal has changed was conditioned by changing approaches to rural areas development. At the same time, the role of local resources in rural development concepts has been different and changed according to the concepts. The above-mentioned are overlaid by the issue of the use of local resources in village renewal actions. That issue has also been dynamic in the history of village renewal. There is no doubt that those three subjects (village renewal, rural development and local resources), strongly correspond to each other. We have decided to undertake the description of these relations in order to systematise the state of art in the common ground for these three issues. The main aim of the paper wasto present the embeddedness of village renewal in rural development paradigms, partly in regional/local development paradigms, and in other scientific concepts, as well as to present the role of local resources in village renewal processes over the years. The paper, based on literature review, is theoretical and open to further debate. The considerations included in the paper indicate that village renewal bases on local resources and simultaneously strengthens them. Local resources are recognised as key in regional/local development. In the light of current scientific concepts, it is a local community who shall decide about the utilisation of these resources, which could use external instruments for this purpose.
24 cm
Keywords: local resources; village renewal; rural areas development; concepts of rural areas development